A hundred horizons : the Indian Ocean in the age of global empire - Sugata Bose (Permanent black, 2006)
"Between 1850 and 1950, the Indian Ocean teemed with people, commodities, and ideas: pilgrims and armies, commerce and labor, the politics of Mahatma Gandhi and the poetry of Rabindranath Tagore were all linked in surprising ways. Sugata Bose finds in these intricate social and economic webs evidence of the interdependence of the peoples of the lands beyond the horizon, from the Middle East to East Africa to Southeast Asia." "In following this narrative, we discover that our usual ways of looking at history - through the lens of nationalism or globalization - are not adequate. The national ideal did not simply give way to inevitable globalization in the late twentieth century, as is often supposed: Bose reveals instead the vital importance of an intermediate historical space, where interregional geographic entities like the Indian Ocean rim foster nationalist identities and goals yet simultaneously facilitate interaction among communities."--BOOK JACKET.